Bilateral musculocutaneous nerve palsy from strength training - Matz, S. O.; Nibbelink, G. (The Physician and Sportsmedicine, 2004)
Musculocutaneous nerve palsy from repetitive biceps curls usually affects only the patient's dominant arm; however, in this case, the patient, an 18-year-old football player, experienced bilateral symptoms. The patient had noted poor performance and a loss of biceps muscle mass before seeking medical care.